PENGARUH KUALITAS PELAYANAN TERHADAP WOM MELALUI KEPUASAN PADA PT. SARANA DEWATA COURIER - Yuni Anita, Ni Luh Nyoman; Bayu Rahanatha, Gede (E-Jurnal Manajemen, 2015)
The increase of business growth in the field of express courier services in Denpasar, createan  intense competition. To be able to survive and win the customers, the company must be able to provide services that make their customers satisfy, thus will create word of mouth as an effective marketing profitable for the company. This research was conducted in Denpasar, the sample conclude 130 respondents and taken using purposive sampling method. Data then collected using questionnaires.This study use"Structural Equation Model"(SEM) as the analysis method. The results showed that the service quality affect"word of mouth" directly and indirectly through customer satisfaction at PT. Sarana Dewata Courier Denpasar.
Keywords: Service Quality, Customer Satisfaction, Word of Mouth